Sex estimation of Brazilian skulls using discriminant analysis of cranial measurements (Research, Society and Development, 2021)
The present study aimed to evaluate the accuracy of cranial measurements for estimation of sex in the Brazilian population and develop discriminant formulas with a reference table to be used as a reference on Brazilian Forensic Anthropology studies. The total sample was comprised of 100 skulls from an osteological collection and 200 computed tomography. The measure’s protocol comprised 51 cranial measurements and it was based on 29 cranial landmarks. The results of the univariate comparison of cranial measurements showed a higher mean for male skulls, except for the following variables: zygoorbital breadth (diff=-2.21), interorbital breadth (diff=-0.72), nasal breadth (diff=-0.19) and palatal breadth (diff=-0.01). The paired test t analysis showed that the variables with the highest sexual dimorphism were maximum cranial length (p